A photo-cleavable polyprodrug-loaded wound dressing with UV-responsive antibacterial property. Issue 45 (8th November 2017) - Pang, Qian; Zheng, Xiaowen; Luo, Yu; Ma, Lie; Gao, Changyou
Abstract : A wound dressing with UV-responsive antibacterial property was prepared by loading a photo-cleavable polyprodrug (LHP) into poly(vinyl alcohol)/sodium alginate (PVA/SA) wound dressing to overcome the overuse of antibiotics. Abstract : The development of antibiotic-loaded wound dressings is of great importance in wound healing and infection treatment. However, in traditional antibiotic-loaded wound dressings, antibiotics are released uncontrollably from the dressings primarily by passive diffusion. The overuse of antibiotics may lead to drug resistance and side effects, which could hinder the healing process. To overcome these shortcomings, a wound dressing with UV-responsive antibacterial property was developed in this study. Levofloxacin (LF) was first conjugated to amine-terminated poly(ethylene glycol) through a photolabile ortho -nitrobenzyl linker to obtain a photo-cleavable polyprodrug (LHP), which was then loaded into a poly(vinyl alcohol)/sodium alginate (PVA/SA) wound dressing. Compared to the PVA/SA dressing, the LHP-loaded dressing showed larger swelling capacity and retained good cytocompatibility. It was found that LF could be cleaved from LHP under UV irradiation at 365 nm and released gradually from the wound dressing with an increase in UV irradiation time. The antibacterial zone test proved that the LHP-loaded wound dressing possessed UV-responsive antibacterial properties against Staphylococcus aureus .